Built environment and physical activity: a brief review of evaluation methods - Adriano Akira Ferreira Hino; Rodrigo Siqueira Reis; Alex Antonio Florindo (Revista Brasileira de Cineantropometria e Desempenho Humano, 2010)
There is strong evidence indicating that the environment where people live has a marked influence on physical activity. The current understanding of this relationship is based on studies conducted in developed and culturally distinct countries and may not be applicable to the context of Brazil. In this respect, a better understanding of methods evaluating the relationship between the environment and physical activity may contribute to the development of new studies in this area in Brazil. The objective of the present study was to briefly describe the main methods used to assess the relationship between built environment and physical activity. Three main approaches are used to obtain information about the environment: 1) environmental perception; 2) systematic observation, and 3) geoprocessing. These methods are mainly applied to evaluate population density, mixed land use, physical activity facilities, street patterns, sidewalk/bike path coverage, public transportation, and safety/esthetics. In Brazil, studies investigating the relationship between the environment and physical activity are scarce, but the number of studies is growing. Thus, further studies are necessary and methods applicable to the context of Brazil need to be developed in order to increase the understanding of this subject.